ANALISIS EFISIENSI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBELUM DAN SESUDAH BERLAKUNYA UNDANG-UNDANG PPH TAHUN 2008 - Winarti Winarti; Herry Laksito (Diponegoro Journal of Accounting, 2014)
The primary objective of this study was to test the efficiency of listed manufacture company before and after the change of Income Tax Act 2008. The variables used to measure efficiency is Data Envelopment Analysis (DEA) is a multi-factor productivity analysis model for measuring the efficiency of a group of homogenuous Decision Making Unit (DMU). Data Envelopment Analysis (DEA) is an important tool that can be used to evaluate and improve the performance of the manufacture or service businesses. In addition, researchers aimed to examine the response to changes in manufacturing companies Act No.. 36 Year 2008 on Income Tax due to a reduction in income tax rates between 2009 and the Agency for the year 2010 is the year 2009 and by 28% in 2010 down to 25% of the earnings management behavior. The sample of this study is manufacturing companies listed in Indonesia Stock Exchange, which has published its financial statements from the years 2007-2011. The method of analysis in this study using different test analysis to determine the effect of independent variables (Discretionary accruals, return on assets, efficiency) of the dependent variable (the efficiency of manufacturing companies).The results of hypothesis testing with the Wilcoxon test showed no sign rating differences in efficiency before and after the change in the Income Tax Act. Manufacture company before and after the change in the Income Tax Act of 2008 did not prove to the management of discretionary accruals to earnings management.